Building University Schools in Teacher Education Programmes. Guidelines and Suggestions. Intellectual Output 4 in the EdUSchool Project - Lazarová, Bohumíra; Pol, Milan; Moškvan, Vladimír; Gerholz, Karl-Heinz; Neubauer, Jörg; Reinke, Hannes; Wagner, Anne; Marko, Nils; Seitle, Johannes; Wilbers, Karl; Midjo, Bjorn Ivar; Smith, Kari; et al. (Masaryk University Press, 2021)

Educational module for teachers and leaders in University Schools. Intellectual Output 3 in the EdUSchool Project - Smith, Kari; Stenoien, Ingrid; Midjo, Bjorn Ivar; Gerholz, Karl-Heinz; Neubauer, Jörg; Reinke, Hannes; Wagner, Anne; Marko, Nils; Seitle, Johannes; Wilbers, Karl; Lazarová, Bohumíra; Pol, Milan; et al. (2021)

Institutional description of University School Concepts in Europe. Intellectual Output 1 in the EdUSchool Project - Gerholz, Karl-Heinz; Neubauer, Jörg; Reinke, Hannes; Wagner, Anne; Lazarová, Bohumíra; Pol, Milan; Bader, Christina; Marko, Nils; Wilbers, Karl; Midjo, Bjorn Ivar; Stenoien, Ingrid; Smith, Kari; et al. (2020)
The professionalization of teacher education is a much discussed topic in Europe (Smith 2016, Cain 2015). A large part of this discussion is the relationship between theory and practice, but above all the transfer from theory to practice and vice versa (Gerholz & Wilbers 2018). The first focus is on how to provide students with practical skills and knowledge during their professional education. This has recently led to a ‘change in practice’ in teacher education. The second focus is on how scientific insights can be implemented in everyday school life and how current challenges facing schools can be incorporated into scientific research. With this in mind, closer cooperation between schools and universities on the institutional and organizational level seems to be a promising opportunity to build up stable, partnership-based theory-practice-cooperation. An innovative concept are so-called University Schools, comparable to university hospitals, in which teaching and research are carried out simultaneously and can be productively combined (Gerholz & Wilbers 2018, Smith 2016). The intention of University Schools is to build strategic alliances between universities and schools in order to educate future teachers in study programmes and at the same time cooperate in research and school development processes (EdUSchool proposal 2018).

The EdUSchool triple helix. EdUSchool Good Practices. Intellectual Output 2 in the EdUSchool Project - Bader, Christina; Marko, Nils; Wilbers, Karl; Gerholz, Karl-Heinz; Neubauer, Jörg; Reinke, Hannes; Wagner, Anne; Lazarová, Bohumíra; Pol, Milan; Midjo, Bjorn Ivar; Stenoien, Ingrid; Smith, Kari; et al. (2020)